Sohn-Rethel et le projet d’une critique matérialiste de la connaissance - Vincent Chanson (Recherches Germaniques)
This article addresses Alfred Sohn-Rethel’s materialist critique of epistemology from the perspective of its elaboration according to the model of the critique of Marxian political economy. More specifically, it examines a conceptual perspective that unfolds in a double relationship – of critique and fidelity – to the Kantian model. It does so, moreover, to the extent that Sohn-Rethel’s critique of real abstraction seems to belong to a strain of views that descend from transcendental idealism. Thus, it poses the question of what might belong to a dialectic of social forms in Sohn-Rethel’s thought. Yet this dialectic in the critique of political economy implies a Hegelian moment that seems to be overlooked by the author of Warenform und Denkform.